Cause of a Lower‐Tropospheric High‐Ozone Layer in Spring Over Hanoi. Issue 10 (13th May 2022) - Ogino, S.‐Y.; Miyazaki, K.; Fujiwara, M.; Nodzu, M. I.; Shiotani, M.; Hasebe, F.; Matsumoto, J.; Witte, J.; Thompson, A. M.; Nguyen‐Thi, H. A.; Nguyen, T. V.
Abstract: The ozonesonde observations in Hanoi, Vietnam, over 14 years since 2004, have confirmed an enhancement in lower tropospheric ozone concentration at about 3 km altitude in the spring season. We investigated the evolution of the ozone enhancement from analysis of meteorological data, backward trajectories, and model sensitivity experiments. In spring, air masses over Hanoi exhibit strong height dependence. At 3 km, the high‐ozone air masses originate from the land area to the west of Hanoi, while low‐ozone air masses below about 1.5 km are from the oceanic area to the east. Above 4 km, the air masses are mostly traced back to the farther west area. The chemical transport model simulations revealed that precursor emissions from biomass burning in the inland Indochina Peninsula have the largest contribution to the lower tropospheric ozone enhancement, which is transported upward and eastward and overhangs the clean air intrusion from the ocean to the east of Hanoi. At this height level, the polluted air has the horizontal extent of about 20° in longitude and latitude. The polluted air observed in Hanoi is transported further east and widely spread over the northern Pacific Ocean. Plain Language Summary: Ozone in the lower atmosphere acts as an air pollutant and is one of the strong greenhouse gases. Understanding chemical and transport processes that control ozone variations provide important implications for the origin of air pollution and for climate change. In the past 20 years, the global tropospheric ozone amount has increased in the tropics and subtropics, with particularly large increases in Southeast Asia. We analyze a seasonal enhancement in ozone over Hanoi, Vietnam, using the 14‐year record of upper air ozone measurements that began in 2004. The measurements reveal high levels of ozone particularly during the spring that peak at around 3 km. Numerical model simulations show that agricultural burning in the inland Indochina Peninsula is the major contributor to these high ozone amounts that are transported upward and eastward and overhang the clean air from the ocean to the east of Hanoi. Over time, the high‐ozone air observed in Hanoi is transported further east and widely spread over the northern Pacific Ocean. The identified source of the ozone enhancements and its three‐dimensional distribution provide new insights into the impact of agricultural burning over Southeast Asia on large‐scale ozone distributions and are relevant to global air quality and climate studies. Key Points: Ozonesonde observations in Hanoi, Vietnam, for about 14 years since 2004 display an ozone enhancement at ∼3 km altitude in March–April Enhanced ozone air at ∼3 km originates from burning areas west of Hanoi whereas low‐ozone near‐surface air is marine from the east Model experiments show biomass fires in the Indochina Peninsula are the cause of Hanoi's enhanced ozone